Contribution to the study of the mesodermal ecto CNS barrier in certain disease processes, particularly in schizophrenia - Espino, Delfín C. (1927)
Inspired, especially in investigations Goldmann Schapfer, L. Stern, C. Von Monakow and his disciples, about the great preponderance has taken in recent years the study of the choroid plexus and in general, the barrier ecto mesodermal, as a complex functional unit that protects the central nervous system noxae altering all normal operation; I have seen fit to address even if only in a general study of pulsating current, which has much interest in psychiatry and general medicine.